Pelatihan dan Pendampingan Literasi Bahasa Inggris pada Kelompok Anak-Anak di Desa Pudun Julu - Khairunnisah - Khairunnisah; Happy Sri Rezeki Purba; Husniah Ramadhani Pulungan (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2022)
AbstractThis topic was chosen because a forum for children in Pudun Julu to explore English literacy in the surrounding environment is still limited. The team of dedication to society offers a method of service with material related to time in two stages. Phase I includes providing material, reading practice, and material comprehension. Furthermore, phase II includes assistance by practicing every child's reading, pronouncing vocabulary well, answering the quiz, and speaking practices alternately. The result of this dedication to society activity is an increased understanding of insight and motivation of children’s English literacy in Telling Time. The urgency of the results of this study is the awareness of children about the importance of English literacy for their future through discipline in respecting time. Thus, the children have gained a reinforcement of literacy in the form of the application of time discipline in English appropriately, properly, and correctly.